The Storm in Someone’s Mind - Galindo Caro, Diana Paola (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Depression has a great influence on the mental health of young people today. On the one hand,there are feelings and emotions that the person harbors in a strict way and that are evidencedespecially through sadness. On the other hand, there are the physical, psychological, and socialchanges that lead to being distracted, thoughtful, and absent. All these changes on mental healthinfluence relationships, especially family relationships and the level of commitment of the family thatis involved in the change.